Hypothalamic neuronal histamine mediates the thyrotropin-releasing hormone-induced suppression of food intake(1) - Gotoh, Koro (Blackwell Publishing Ltd, 2007)
We examined the involvement of thyrotropin-releasing hormone (TRH) and TRH type 1 and 2 receptors (TRH-R1 and TRH-R2, respectively) in the regulation of hypothalamic neuronal histamine. Infusion of 100 nmol TRH into the rat third cerebroventricle (3vt) significantly decreased food intake (p < 0.05) compared to controls infused with phosphate- buffered saline. This TRH-induced suppression of food intake was attenuated partially in histamine-depleted rats pre-treated with α-fluoromethylhistidine (a specific suicide inhibitor of histidine decarboxylase) and in mice with targeted disruption of histamine H1 receptors. Infusion of TRH into the 3vt increased histamine turnover as assessed by pargyline-induced accumulation of tele-methylhistamine (t-MH, a major metabolite of neuronal histamine in the brain) in the tuberomammillary nucleus (TMN), the paraventricular nucleus, and the ventromedial hypothalamic nucleus in rats. In addition, TRH-induced decrease of food intake and increase of histamine turnover were in a dose-dependent manner. Microinfusion of TRH into the TMN increased t-MH content, histidine decarboxylase (HDC) activity and expression of HDC mRNA in the TMN. Immunohistochemical analysis revealed that TRH-R2, but not TRH-R1, was expressed within the cell bodies of histaminergic neurons in the TMN of rats. These results indicate that hypothalamic neuronal histamine mediates the TRH-induced suppression of feeding behavior.